The Challenges of Implementing Eclectic Method in Teaching Speaking faced by English Instructors at Global Learning Center - Nathania, Stella; Luardini, Maria Arina; Asi, Natalina (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
This study was focused on the challenges in implementing eclectic method faced by English instructors at one of the non-formal educations in Palangka Raya, namely Global Learning Center (GLC). The English instructors used eclectic methods to maximize the teaching and learning process in order to achieve the learning goals. The implementation of eclectic method is still new and there is no research about it yet in Palangka Raya. This study intended to investigate the challenges of implementing it in non-formal education. To obtain the objective, the researcher used descriptive qualitative design. The descriptive used to provide rich descriptive details of the challenges in implementing eclectic method. The data were collected through interview and documentation. The result data analysis was found four challenges when implementing the eclectic method, they were (1) managing the time, (2) students’ gap and diversity, (3) designing appropriate lesson plan using eclectic method, and (4) motivating the students to speak. Hopefully, this research can give an insight for teachers and other English course to know the challenges before implementing the eclectic method. They need to be well-prepared in combining several methods in each learning process with considering the allocation time, variation of student backgrounds, and the strategy to motivate the students. For the other researcher, this research is still widely open for those who want to investigate and examine deeply about eclectic method. Keywords: challenges, eclectic method, speaking